1991
DOI: 10.1007/bf00852836
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of formula with sodium polystyrene sulfonate to reduce dietary potassium intake

Abstract: Sodium polystyrene sulfonate (SPSS) is commonly administered for the acute and chronic treatment of hyperkalemia. Its oral intake is complicated by poor compliance due to multifaceted reasons. We therefore analyzed a method of reducing potassium (K) in formula by pretreatment with SPSS. If effective, this would bypass complications of enterally administered SPSS and provide low-K formula. Thirteen formulas and nutritional supplements were pretreated with SPSS to determine if one could bind K and provide formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 16 publications
3
41
0
1
Order By: Relevance
“…A similar reduction of the potassium concentration has been reported with the use of sodium polystyrene sulphonate [1]. In that study an important and undesirable increase of the sodium concentration of the formulas was observed (up to 84mmol/l in orange juice and 101mmol/1 in whole milk) resulting in a high sodium load to the patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A similar reduction of the potassium concentration has been reported with the use of sodium polystyrene sulphonate [1]. In that study an important and undesirable increase of the sodium concentration of the formulas was observed (up to 84mmol/l in orange juice and 101mmol/1 in whole milk) resulting in a high sodium load to the patients.…”
Section: Discussionsupporting
confidence: 78%
“…They have an unpleasant taste and may cause constipation, and sometimes even bowel obstruction. Pretreatment of potassium-containing fluids with sodium polystyrene sulphonate may lower the potassium content considerably, but gives a noticeable increase in sodium concentration [1]. In the present study our experience with calcium polystyrene sulphonate is presented.…”
Section: Introductionmentioning
confidence: 83%
“…5 FOOD PRE-TREATED WITH SEVELAMER TO REDUCE PHOSPHATE Pretreatment of formula or breast milk has been performed before to reduce dietary intake of phosphate or potassium and to avoid the practical disadvantages or potential side effects of taking the medication. For potassium, Bunchman et al (27) found that sodium polystyrene sulfonate effectively reduced the potassium content in several formulae. However, sodium increased disproportionally, and calcium and magnesium decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The Na + -charged polystyrene sulfonate (Kayexalate) used orally while ingesting food to absorb dietary K + led to gastrointestinal (GI) side effects and release of Na + that could lead to excess Na + absorption [8][9][10][11][12][13][14][15]. The Ca 2+ -charged cation exchangers did not release Na + in the GI system but had significantly lower K + binding capacity [15][16]. New K + binding compounds such as Veltassa (Patiromer) and ZS-9 will potentially replace Kayexalate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lowering the K + content of food before it is consumed may be a helpful approach to improve the variety of the diet of kidney patients. Towards this goal, large scale ion-exchange column chromatography can be used to remove K + from juices without pulp [15][16][17][18][19][20][21], however this approach has not been utilized to create commercial products.…”
Section: Introductionmentioning
confidence: 99%